Do Effects of Social-Emotional Learning Programs Vary by Level of Parent Participation? Evidence From the Randomized Trial of INSIGHTS. Issue 3 (2nd July 2016) - McCormick, Meghan P.; Cappella, Elise; O'Connor, Erin; Hill, Jennifer L.; McClowry, Sandee
ABSTRACT: Social-Emotional Learning (SEL) programs aim to improve students' social-emotional competencies in order to enhance their achievement. Although SEL programs typically implement classroom curricula, some programs also include a component for parents. Yet, little is known about the types of parents likely to participate in services, and whether parent participation moderates program effects on student outcomes in low-income urban schools. This article aims to fill these gaps in the literature using data from the randomized trial of the SEL program INSIGHTS into Children's Temperament ( N = 435 parent/child dyads), which was conducted in 22 low-income urban elementary schools during children's kindergarten and first-grade year. Descriptive findings revealed that children at lower risk for poor achievement had parents who were more likely to participate in program services. In addition, findings from inverse probability of treatment-weighting models demonstrated larger effects of INSIGHTS on academic, attentional, and behavioral outcomes for children whose parents participated at lower rates. Implications for prevention science and SEL program implementation and scale-up are discussed.